Diffusion‐weighted MRI does not reflect kidney fibrosis in a rat model of fibrosis. Issue 4 (28th January 2015) - Boor, Peter; Perkuhn, Michael; Weibrecht, Martin; Zok, Stephanie; Martin, Ina V.; Gieseke, Jürgen; Schoth, Felix; Ostendorf, Tammo; Kuhl, Christiane; Floege, Jürgen
<x xml:space="preserve">Abstract</x> Purpose To assess the apparent diffusion coefficient (ADC) derived from diffusion‐weighted (DW) magnetic resonance imaging (MRI) as a specific marker of renal fibrosis in rats with unilateral ureteral obstruction (UUO). Materials and Methods Thirteen rats were analyzed in group 1 (n = 4), group 2 (n = 3), and group 3 (n = 6) and measured using a clinical 3.0T MR scanner. Groups 1 and 2 were used to establish the final imaging protocols for group 3. DW imaging with four b‐values (0, 50, 300, 800 s/mm2) was conducted before UUO, at days 3 and 5 after UUO, after release of the obstruction, and after sacrifice. Renal cortical ADCs were correlated with histological and ultrastructural analyses. Results ADC values of group 3 are shown as mean ± standard deviation of [10−3mm2/s]. On day 5, in vivo cortical ADC of obstructed fibrotic kidneys was significantly reduced compared to unobstructed kidneys (1.4 ± 0.086 vs. 1.535 ± 0.087, P = 0.0018). Postmortem ADC dropped by 50% and was significantly increased in obstructed vs. unobstructed kidneys (0.711 ± 0.094 vs. 0.566 ± 0.049, P = 0.0046). Histopathology of obstructed kidneys showed tubular dilation, tubular cell atrophy, and expansion of the interstitial space. Postmortem ADC correlated tightly with tubular lumen area (r = 0.9, P < 0.001), fibronectin (r = 0.8, P = 0.003), collagen type I (r = 0.73, P = 0.007), and interstitial expansion (r = 0.69, P = 0.013). Conclusion Compared to the in vivo measurements, postmortem renal ADCs were considerably reduced and, unlike in vivo, fibrotic kidneys exhibited consistently higher ADC compared to healthy kidney parenchyma. Our data suggest that in vivo ADC is unlikely to be a direct measure of renal fibrosis. J. Magn. Reson. Imaging 2015;42:990–998.